Assessment of a novel numerical model for combustion and in-flight heating of particles in an industrial furnace. Issue 6 (December 2018) - Gerhardter, H.; Prieler, R.; Mayr, B.; Landfahrer, M.; Mühlböck, M.; Tomazic, P.; Hochenauer, C.
Abstract: The key factors for efficient in-flight particle heating in a combusting flow were investigated within this paper for the development of a novel boiler slag bead production furnace. A natural gas fired industrial burner with a thermal input of 1.2 MW was thus evaluated using Computational Fluid Dynamics (CFD). The steady laminar flamelet model (SFM) and a detailed chemical reaction mechanism, considering 25 reversible chemical reactions and 17 species were used to account for the steady-state gas phase combustion. Measurements of gas temperature and flow velocity within the furnace were found to be in good accordance with the numerical results. In the second step, sintered bauxite beads were injected into the furnace as an experimental material and heated up in flight. The particle heating characteristics were investigated using the Discrete Phase Model (DPM). The computational results of the particle laden flow raised the issue that convective heat transfer is a key factor for efficient particle heating. At the burner chamber outlet, the temperature of a particle which had been injected into the burner flame was 178 K higher compared to a particle, which trajectory led through zones with lower gas temperatures. Highlights: Calculations and experiments were performed on a 1.2 MW industrial furnace. In-flame temperature measurements and numerical results are compared. The main influence factors for particle heating were evaluated. Numerical calculation of convective and radiative particle heat transfer. Convection plays an important role for in-flight heating of particles.